2012
DOI: 10.1111/j.1743-6109.2012.02913.x
|View full text |Cite
|
Sign up to set email alerts
|

Separate or Combined Treatments with Daily Sildenafil, Molsidomine, or Muscle‐Derived Stem Cells Prevent Erectile Dysfunction in a Rat Model of Cavernosal Nerve Damage

Abstract: Introduction.  Long‐term daily administration of phosphodiesterase type 5 (PDE5) inhibitors in the rat prevents or reverses corporal veno‐occlusive dysfunction (CVOD) and smooth muscle cell (CSMC) loss and fibrosis, in both aging and bilateral cavernosal nerve resection (BCNR) models for erectile dysfunction. In the aging rat model, corporal implantation of skeletal muscle‐derived stem cells (MDSC) reverses CVOD. Nitric oxide (NO) and cyclic guanosine monophosphate can modulate stem cell lineage. Aim.  To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 48 publications
1
40
0
1
Order By: Relevance
“…No non-diabetic MDSC were isolated and tested, since this would require a different non-allogeneic strain as a source, the LZ rats, thus complicating the comparison and also the statistics and the study itself if a sixth experimental group would have been added. So, the ED-SC was taken as a control, considering that in addition, the non-diabetic MDSC have already been shown by us to ameliorate corporal SMC loss and fibrosis and CVOD in non diabetic rats (31,32,47). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No non-diabetic MDSC were isolated and tested, since this would require a different non-allogeneic strain as a source, the LZ rats, thus complicating the comparison and also the statistics and the study itself if a sixth experimental group would have been added. So, the ED-SC was taken as a control, considering that in addition, the non-diabetic MDSC have already been shown by us to ameliorate corporal SMC loss and fibrosis and CVOD in non diabetic rats (31,32,47). …”
Section: Resultsmentioning
confidence: 99%
“…MDSC were isolated from the hind limb muscles from the two OZ rat groups (n=2/group), using the preplating procedure, a validated method for MDSC isolation, as in our previous reports for mice and Fisher 344 rats (3135). Preplate fraction 6 (pP6) is the cell population containing MDSCs, that was subjected to Sca 1 selection and flow cytometry as described.…”
Section: Methods and Main Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…71 A study performed by Kovanecz et al combined the current treatment strategy for postprostatectomy ED, the daily use of a PDE5i, with stem cells. 72 Specifically, they investigated the effects of sildenafil at low doses, alone or in combination with MDSCs or the nitric oxide donor, molsidomine, in treating veno-occlusive disease in the bilateral cavernous nerve resection rat model. The results of the study indicated that a sustained administration of sildenafil at medium and low doses prevents veno-occlusive disease after nerve resection, and reduces collagen deposition in the corpora cavernosa.…”
Section: Enhancing the Efficacy Of Stem Cellsmentioning
confidence: 99%
“…Later, Qiu et al established RiED as a target for SC therapy and showed that IC injection of stem cells was able to treat both acute and chronic CN injury-induced ED 65, 67. Kovanecz et al showed that IC injection of SkMSC (xenogeneic mouse mesenchymal stem cells) alone or in combination with oral sildenafil was able to normalize erectile function in rats with CN injury 68 . There has been a lot of progress in this field of research.…”
Section: History Of Ed Treatmentmentioning
confidence: 99%